Optimization of lipase enzyme activity and variables of fermentation conditions containing grape juice substrate in Aspergillus niger culture medium - Nima Zargaran; Reza Habibipour; Narges Ghobadi (بیولوژی کاربردی, 2022)
Objective: Lipase enzyme is one of the important enzymes in food, detergent and textile industries. Also, today, industries related to this enzyme such as processing of organic materials, synthesis of biosurfactants, beverages and cosmetic, pharmaceutical and food industries have expanded significantly. In this regard, the aim of the current research is to optimize the activity of lipase enzyme and the variables of fermentation conditions containing grape juice substrate in Aspergillus niger culture medium. Materials and methods: In this research, for the first time, in order to achieve the maximum activity of the enzyme in the culture medium containing the carbon source of grape juice, the effective variables in the fermentation process of Aspergillus niger, i.e. temperature, acidity, concentration of grape juice and nitrogen source (yeast extract-peptone) with the help of Design Expert software was optimized. Findings: The acidity equal to 7.5, the amount of concentration of grape juice and the combination of yeast extract and peptone (with a ratio of two to one) were obtained with 1.5 and 0.75%, respectively. Lipase activity after optimizing the conditions of the culture medium was equal to 17.694 U/ml. Conclusion: Aspergillus niger records significant lipase activity in the culture medium with the factors of temperature, concentration of grape juice and yeast extract and peptone in its optimal amount and acidity equivalent to 7.5. Therefore, the carbon and nitrogen sources used in this research are suitable sources for use in the culture medium of this microorganism to produce lipase enzyme.